2021
DOI: 10.1016/j.cej.2021.128553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of agitation mode (mechanical, ultrasound and microwave) on uranium sorption using amine- and dithizone-functionalized magnetic chitosan hybrid materials

Abstract: Magnetic chitosan nanoparticles, activated by glycidyl methacrylate, can be functionalized by grafting dieth-ylenetriamine (DETA) and dithizone for improving U(VI) sorption at pH around 5. The physicochemical prop-erties of the materials have been characterized by a wide variety of analytical techniques. Uranyl sorption increases with the pH (progressive deprotonation of amine and sulfur groups). Uptake kinetics are controlled by the agitation mode: the equilibrium time is reduced while using ultrasonic treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 122 publications
(127 reference statements)
0
22
0
2
Order By: Relevance
“…However, recent studies have clearly showed the beneficial effect using alternative modes of agitation. The sorption performance can be strongly improved by application of ultrasonic treatment (UT) [92] or microwave activation [93]); in the latter case the kinetic rate is drastically accelerated while the equilibrium sorption is dramatically decreased.…”
Section: Sonication-assisted Sorptionmentioning
confidence: 99%
“…However, recent studies have clearly showed the beneficial effect using alternative modes of agitation. The sorption performance can be strongly improved by application of ultrasonic treatment (UT) [92] or microwave activation [93]); in the latter case the kinetic rate is drastically accelerated while the equilibrium sorption is dramatically decreased.…”
Section: Sonication-assisted Sorptionmentioning
confidence: 99%
“…The thermal degradation of R-Amine and R-Dithizone are relatively close, exhibiting that the residual weights after complete degradation are close to 15 and 11%, respectively. However, DTG curves showed substantial differences between the two sorbents, proving that the water uptake of R-Dithizone was higher in comparison to R-Amine (diphenylthiocarbazone for producing GMA-magnetic/CS-dithizone NPs, R-Dithizone, for comparison with R-Amine sorbent) [ 13 ].…”
Section: Synthetic Routes and Characterizationsmentioning
confidence: 99%
“…Here, this band is “hidden” in the range of 970–900 cm −1 (poorly resolved region). A series of smalls bands at 1343 cm −1 , 826 cm −1 , and 745 cm −1 could be attributed to the ligand of nitrate attached to bound uranyl (−N=O symmetric bending, −N−O out of plane rocking, −N−O symmetric bending, respectively) [ 13 ].…”
Section: Adsorption Evaluationmentioning
confidence: 99%
See 2 more Smart Citations